Pemanfaatan Alat Permainan Edukasi dalam Mengembangkan Kecerdasan Emosional dan Kognitif Anak Usia Dini - Shidqiyah M.Pd (Universitas Islam Lamongan, 2025)
Abstract Building children's emotional intelligence from an early age is important. For this reason, activities in early childhood education are needed that focus on character development. Departing from this background, the author considers this study to be quite important to study. The goals of this study is to find out how effective educational game tools using and what the impact on children's emotion. To find the results of this research, the author used qualitative library methods. Review various important documents relevant to the theme of this study. This study find that; First, there are several types of APE for early childhood to stimulate emotional intelligence, including magic boxes, color blocks, snakes and ladders games, and natural media. Meanwhile, the types of APE for intelligence intelligence consist of APE Technology Digital, APE Wood, and Guess the Picture. Second, the reason APE can be a tool to stimulate intelligence in early childhood is because it has several characteristics, including stimulating growth and development, appropriate to the child's age, creative and attracting attention, useful, safe to use, simple in shape, and supports children to be actively involved. Keywords: Educational game tools, emotional intelligence, character building.